The biography of Dr Hannah-Reeve Sanders, the first female Chief Medical Superintendent of Groote Schuur Hospital - Bloch, Leila R. (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.